PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN SUBANG - ENDANG IRAWAN SUPRIYADI (Prodi Ilmu Administrasi Negara, Universitas Al Ghifari, 2020)
Work motivation in an organization has a very important role in influencing employee performance. The study conducted in Subang at the Ministry of Religion office, the problem facing in the office was employees’ low performance. To strengthen the problem occurs, based on the writer’s opinion related to the work motivation was not developed well in the Office of the Ministry of Religion, Subang. This study using an explanatory survey as a method. Based on the results of writing and simultaneous discussion, it was revealed that the work motivation variables of empirical employees had a big influence on the performance of the Ministry of Religion employees in Subang Regency by 85.8%. The conclusion about the contribution of the work ability variable of the Ministry of Religion of Subang Regency to the performance of the employees of the Office of the Ministry of Religion of Subang Regency (Y) was 85.8% while the remaining 14.2% was influenced by other factors.